Meningitis Streptococcus Suis Outbreak Investigation in Blimbing Sari Village, Jembrana Bali - Anggriawan, I Putu Aditya; Artawan Eka Putra, I Wayan Gede; Dwi Adi, Putu (Newinera Publisher, 2024)
The aim of this outbreak investigation is to prevent the spread of the disease, prevent the recurrence of similar cases in the future, ensure that the situation is truly an outbreak, identify the source and method of disease transmission and identify vulnerable areas or populations at risk. The investigation was conducted with interviews to seek related information with the hospital's staff, the patient's family, the health center, the village staff and the animal welfare officer. We examined the medical records of patients and interviewed the doctor on duty and the health center officer, followed by interviewing the patient's family who was hospitalized. Interview with the head of the and the animal health officer was to find out the possible source of infection, pig farming in the village and related condition that enable MSS transmission. There were 5 cases residing in the same village. The patient's medical record indicated acute bacterial meningitis, but no laboratory diagnosis was performed due to limited equipment. The head of the village confirmed the history of processed pork products such as